Coronary Embolism from Prosthetic Aortic Valve due to Incompliant Warfarin Use: A Rare Cause of Acute Coronary Syndrome - Canpolat, Uğur; Şener, Yusuf Ziya; Okşul, Metin; Şahiner, Mehmet Levent; Aytemir, Kudret (European Journal of Therapeutics, 2023)
Acute ST-segment elevation myocardial infarction (STEMI) is a life-threatening condition for which revascularization should be accessed emergently. Most STEMI cases result from atherosclerotic plaque rupture. However, rare causes such as coronary artery dissection, the vasculitic involvement of the coronary arteries, and coronary artery embolism may result in pathophysiological mechanism. This paper presents the case of a young male patient with subacute anterior STEMI secondary to thrombus embolism from prosthetic aortic valve due to incompliant warfarin use.